2020
DOI: 10.1002/ijfe.2150
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the role of neurotransmitters in investment decision: A proposed constructs

Abstract: The purpose of this study is to develop a reliable and valid neurotransmitter's measurement scale. The developed scale would be instrumental in studying the role of neurotransmitters in financial decisions making. A threefold approach was used to develop and validate the scale. The first stage was a qualitative exploratory step for item generation, second initial purification of the stage 1 findings using exploratory factor analysis, and third was validation of the scale using confirmatory factor analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…Drawing upon the studies of Mubarik (2015), Carpenter (2018), Mubarik et al. (2018), Khan and Mubarik (2022) and Mubarik et al. (2021a, b), we adopted a fourfold approach to develop the construct.…”
Section: Methodology: Process Of Construct Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing upon the studies of Mubarik (2015), Carpenter (2018), Mubarik et al. (2018), Khan and Mubarik (2022) and Mubarik et al. (2021a, b), we adopted a fourfold approach to develop the construct.…”
Section: Methodology: Process Of Construct Developmentmentioning
confidence: 99%
“…It is found that extensive workload in a job always delivers a poor performance of employees and develop health problems which compel them to quit their firms (Deery and Jago, 2015). Mubarik (2015), Carpenter (2018), Mubarik et al (2018), Khan and Mubarik (2022) and Mubarik et al (2021a, b), we adopted a fourfold approach to develop the construct. In the first stage, relevant dimensions and sub-dimensions of TMSs are explored through comprehensive review of literature.…”
Section: Measuring Talent Managementmentioning
confidence: 99%
“…Along with behavioral factors, neurological features significantly influence investors’ financial decisions (Khan & Mubarak, 2020; Sapra et al, 2012). Information processing capacity of the human brain and the underlying neurological features vary from human to human, leading to diversities in investment decisions and profit expectations (Sahi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the link between psychology and financial decision‐making is advancing rapidly – see, for instance, the recent study by Khan and Mubarik (2020) on the role of neurotransmitters (chemical signals in the brain). The fact that emotions influence financial decisions is now accepted as incontrovertible and has the scope to explain many instances of apparently puzzling retail investor behaviour.…”
Section: Introductionmentioning
confidence: 99%